Reviews (New blackfriars, 1980)
Book reviewed in this article: SON OF MAN, The Interpratation and Influence of Daniel 7, by Maurice Casey. CENTRED ON CHRIST. An Introduction to Monastic Profession by A. Roberts. RICH MAN, POOR MAN - AND THE BIBLE by Conrad Boerma. POVERTY AND EXPECTATION IN THE GOSPELES by David L. Mealand.